Verpleegkundige-pasiënt kommunikasie - L.R. Uys (AOSIS, 1980)
In communication between nurse and patient two types of interaction are often not fully utilised, namely emotionally supportive conversations and patient-teaching. When these performance problems are analysed, their multicausal nature is discovered and possible remedial steps proposed.